How Veterans Make Meaning of the College Choice Process in the Post-9/11 Era - Derek M. Abbey (The University of Alabama, 2022)
The Post-9/11 GI Bill was implemented in 2009. Since then, more than 1.9 million people have used the benefits afforded by the bill to attend college, and more than $90 billion has been paid to institutions of higher learning and Post-9/11 GI Bill beneficiaries. During this time, the types of colleges that veterans attend as well as the educational models they select have shifted. Veterans are more likely to utilize online or distance education models. Additionally, veterans attend for-profit universities at an increasing and greater rate than do their nonveteran counterparts. These shifts differ from the trends observed among the general population. The purpose of this study was to learn from veterans how they make sense of decision-making related to college choice prior to matriculation into a 4-year institution. Qualitative methods were utilized to examine the lived experiences of 12 post-9/11-era U.S. Navy and U.S. Marine Corps student veterans during the college choice process. The experiences shared by the participants in this study were used to further examine and critique an established theory of college selection. This study provides practitioners and academics with insight into how to better engage with this diverse and unique community of prospective students on and off campus through greater understanding of how they make meaning of the college choice process.